Resiko Transaksi Bisnis Syariah Baitul Maal Wat Tamwil Studi Kasus Produk Pembiayaan - Majid Toyyibi, Abdul; Mawardi, Imam (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
Abstract: In BMT, risk is identical with financing and risk is like an enemy that cannot be abandoned, must be fought and watched out for. Fighting and being wary of is meant so that there is an analysis process in accordance with applicable regulations carried out by certain parties such as BMT for policy purposes in determining the results of the analysis of financing. Then from here used the type and approach is qualitative by looking at case studies or events in the field until from the results of interviews and documentation, data analysis is carried out so that the data can be accounted for the validity of the data. From this research, it was found that BMT has tips to avoid high risk, at least there are preventive actions as a reference for generating a financing that indicates a risk.